2021
DOI: 10.3389/fimmu.2021.713158
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging NKG2D Ligands in Immuno-Oncology

Abstract: Immune checkpoint inhibitors (ICI) revolutionized the field of immuno-oncology and opened new avenues towards the development of novel assets to achieve durable immune control of cancer. Yet, the presence of tumor immune evasion mechanisms represents a challenge for the development of efficient treatment options. Therefore, combination therapies are taking the center of the stage in immuno-oncology. Such combination therapies should boost anti-tumor immune responses and/or target tumor immune escape mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 352 publications
(332 reference statements)
0
57
0
1
Order By: Relevance
“…The expression of cell surface ligands may be altered by various stimuli or stressors. For example, NKG2D ligands are upregulated by chemotherapy, radiation, and inflammation [ 26 , 27 ]. We investigated whether VPA, inflammatory cytokines (IFN-γ plus TNF-α), 5-AZA, GEM, and ionizing radiation (two gray) could induce the expression of NKp44 ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of cell surface ligands may be altered by various stimuli or stressors. For example, NKG2D ligands are upregulated by chemotherapy, radiation, and inflammation [ 26 , 27 ]. We investigated whether VPA, inflammatory cytokines (IFN-γ plus TNF-α), 5-AZA, GEM, and ionizing radiation (two gray) could induce the expression of NKp44 ligands.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of CAR T-cell therapy also depends on the expression levels of ligands on the surface of tumor cells. NKG2D ligands are induced by various inflammatory stimuli or stresses [ 26 , 27 ]. The upregulation of ligands can enhance the effectiveness of CAR T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This intrinsic killing despite the absence of TCR engagement emerges due to high expression levels of NK activating receptors in iNKT cells for potent NK-mediated cytotoxicity ( Figures 2A, B ) ( 50 , 51 ). The capacity of iNKT cells to target TAMs through two distinct pathways provides an attractive method to reengineer the tumor microenvironment and stimulate endogenous CD8 cytotoxic T cells and NK cells ( 52 ). Another study reported that neuroblastoma TAMs were capable of cross-presenting neuroblastoma-derived endogenous glycosphingolipids from the TME, which could specifically activate iNKT cells and induce iNKT cell-mediated TAM killing ( 45 ).…”
Section: Targeting the Tumor Microenvironment Using Inkt Cellsmentioning
confidence: 99%
“…NKG2D, an activating receptor expressed on the surface of NK cells and CD56+ and CD8+ T cells, plays a critical role in the innate immune system and is involved in the recognition and killing of virus-infected cells and tumor cells by NK cells [ 134 ]. NK cells are a preliminary factor for immune surveillance and tumor growth inhibition in the body’s immune system and can terminate tumor cells without antigen stimulation [ 135 ].…”
Section: The Molecular Mechanisms Of Immunosuppressive Signaling Acti...mentioning
confidence: 99%